Investigação de design de filtro manga através da técnica de CFD - Marques, Felipe Bezerra (2017)
The CFD techniques were applied to the design study of the Bag Filter. The goal of using this tool is due to its low cost, in relation to experimental tests, reliability and response time. Therefore, a study was carried out to determine the influence of the air inlet design, input velocity variation and bag suppression to make an analysis of how these variables influence the fluid dynamics of the filter. In order to evaluate the performance of the bag filters, three different feeding positions were simulated, with the variation of the inlet velocity to evaluate the greater utilization of the medium filter area and the change in the disposition of the filter media. In order to do so, we used the single-phase isothermal and incompressible flow model with the turbulence being treated by the realizable k-ε model. It could be concluded that the Single feed presented a more homogeneous distribution of velocity, pressure and with a good use of the filter media, thus representing a more advantageous option of entry when comparing the other proposals. In the case of sleeve suppression, the Simple Alternate configuration presented better performance, with a 43.9% reduction in the area originally proposed, providing better filter utilization, with lower impaction velocities and pressure drop, and distribution More homogeneous velocity in the middle.